Individual Differences in Cognitive Constructs: A Comparison Between American and Chinese Culture Groups - Fan, Gaojie; Carlson, Krista D.; Thomas, Robin D. (Frontiers in Psychology, 2021)
Previous studies on human cognition show that people with different cultural backgrounds may differ in various ways. However, there are other unexplored possibilities for cultural differences including degree of handedness thought to reflect hemispheric coordination, reliance on verbal versus visual representation in problem solving, and working memory capacity both spatial and operational. We assessed each of these using the Edinburgh scale, a validated scale of style of processing, and two automatic working memory span tasks. Participants were either native Chinese students (who spoke Mandarin) or American students. Data showed that culture impacted the set of measures but gender did not and these factors did not interact. Chinese and American students showed the largest difference in their operational working memory. We also examined the pattern of correlations among the measures across the two groups and found differences due to cultural group as well.